Fiscal policy: Why aggregate demand management fails and what to do about it - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2011)
This paper argues for a fundamental reorientation of fiscal policy, from the current aggregate demand management model to a model that explicitly and directly targets the unemployed. Even though aggregate demand management has several important benefits in stabilizing an unstable economy, it also has a number of serious drawbacks that merit its reconsideration. The paper identifies the shortcomings that can be observed during both recessions and economic recoveries, and builds the case for a targeted demand-management approach that can deliver economic stabilization through full employment and better income distribution. This approach is consistent with Keynes's original policy recommendations, largely neglected or forgotten by economists across the theoretical spectrum, and offers a reinterpretation of his proposal for the modern context that draws on the work of Hyman Minsky.
Keywords: E25; J2; J45; I38; 330; labor demand targeting; aggregate demand management; full employment; income inequality; poverty